A Spatial SAR Model in Evaluating Influence of Entrepreneurship and Investments on Unemployment in Poland - Michal Bernad Pietrzak; Adam P. Balcerzak (Institute of Economic Research (IER), 2016)
The research objective of the article is to analyse the impact of changes in the level of entrepreneurship and business investments on unemployment in Poland with the application of spatial econometrics methodology. A spatial SAR model was used to model unemployment, since this phenomenon exhibits the presence of positive spatial dependence. The research was done for 66 regions at NUTS 3 level for the year 2015. In order to provide interpretations of the results measures of average impact such as average direct impact, average indirect impact and average induced impact were applied. The obtained results indicate a positive impact of entrepreneurship and investment on decline in unemployment rate and improvement of Poland's socio-economic situation.
Keywords: C21; E24; 330; spatial econometrics; SAR model; spatial dependence; unemployment; entrepreneurship; investments